Seroprevalence of heartworm (Dirofilaria immitis) in feline and canine hosts from central and northern Portugal. Issue 5 (September 2015) - Vieira, L.; Silvestre-Ferreira, A.C.; Fontes-Sousa, A.P.; Balreira, A.C.; Morchón, R.; Carretón, E.; Vilhena, H.; Simón, F.; Montoya-Alonso, J.A.
Abstract Dirofilaria immitis is endemic in Portugal. Several studies have reported the presence of canine heartworm disease, although no previous studies on feline infections have been published. The aim of this study was to determine the prevalence of D. immitis in cats and dogs from central and northern Portugal. Blood samples from 434 cats were tested for circulating anti-D. immitis and anti-Wolbachia antibodies. Furthermore, 386 dogs were tested for circulating D. immitis antigens. Overall feline seroprevalence was 15%, while canine prevalence was 2.1%. The highest feline seroprevalences of 18.7% and 17.6% were found in Aveiro and Viseu, respectively, while the highest canine prevalences of 8.8% and 6.8% were found in Coimbra and Aveiro, respectively. Cats and dogs showing respiratory signs presented higher prevalences of 24.4% and 17%, respectively, while 50% of cats with gastrointestinal signs were seropositive. The present study confirms the seropositivity of D. immitis in the feline population in central and northern Portugal, and suggests the importance of including heartworm disease in the list of differential diagnoses of cats and dogs showing clinical signs compatible with the disease.